Saberes e práticas da enfermagem na utilização do cateter venoso central de inserção periférica em neonatologia - Jantsch, Leonardo Bigolin (2014)
The nursing knowledge is constituted and strengthens over time with the construction progress of knowledge and recognition of nursing as care science. In the care of newborns in the Neonatal Intensive Care Unit (NICU), the practice of intravenous therapy is frequent and so it requires from team, improvement through the practice of care and the use of technologies that qualify the care. Among the care technologies in intravenous therapy, we highlighted the Peripheral Inserted Central Catheter (PICC) as an instrument for the care and safety in the neonatal intravenous therapy. For both the present study aimed to analyze the knowledge and practices that assist the nursing staff in the PICC management in neonatal intensive care. This is a descriptive study with a qualitative approach. The participants were 11 members of the nursing staff of the NICU in the southern Brazil. The data were generated through semistructured interviews and the data were submitted to the analysis of thematic content. The theoretical framework that supported the interpretation of the results was the patterns of the knowledge in nursing according to Barbara Carper. The study followed the ethical recommendations set out in Brazilian Resolution 466/2012 and was approved by the Ethics Committee of the institution under the number: 13149613.3.0000.5346. From the results constituted three analytical categories, namely: Going beyond to make: the knowledge that permeate the neonatal care in intravenous therapy; Indication of the withdrawal: the knowledge and practices that support the use of PICC in newborns; "I will not try! I'll get" - Knowledge and practices that ensure success during the procedure. We conclude that the knowledge and practice of neonatal nursing management of PICC are permeated by the standards of knowledge established by Carper supporting the Science of Nursing.